Felsőoktatás Kínában 2. : decentralizáció, piacosítás, privatizáció és nemzetközi nyitás - Keczer, Gabriella (Közép-Európai Közlemények, 2016)
In a series of studies I analyze the past and present of Chinese higher education. The topic may be justified by the fact that up to now no comprehensive study has been published in Hungary about the long way China went along from the darkest years of communism to nowadays’ education. In this second paper I summarize the four main phenomena of the reforms after the Mao-era: decentralization, marketization, privatization and internationalization. In the frame of decentralization, the external and internal governance of the universities changed resulting in a power shift from the central level to regional and institutional level. Marketization brought about significant change in the funding of higher education: instead of the state private actors pay for education. Privatization let private actors in the higher education arena, while internationalization means opening up China for foreign institutions and students and letting Chinese students to study abroad. I build my analysis on international literature and statistical data.